Mass spectrometry imaging advances and application in pharmaceutical research - Xiaowei Song; Chao Li; Yifan Meng (Compuscript Ltd, 2022)
Mass spectrometry imaging (MSI) has been shown to be a valuable tool through nearly every stage of the preclinical drug research and development (R&D) pipeline, and even to the early phase of clinical pharmaceutical evaluation. MSI can specifically resolve distributions of a parent drug and its metabolic products across dosed specimens without loss of spatial information, thus facilitating the direct observation of a drug's pharmacokinetic processes, such as absorption, distribution, metabolism, and excretion. MSI can simultaneously visualize hundreds of phenotype molecules, including proteins, glycans, metabolites, and lipids, which have unique distribution patterns and biofunctions across different physiologic regions. This featured specificity in the chemical and physical spaces empowers MSI as an ideal analytical technique in exploring a drug's pharmacodynamic properties, including in vitro/in vivo efficacy, safety, potential toxicity, and possible molecular mechanism. The application of MSI in pharmaceutical research has also been expanded from the conventional dosed tissue analysis to the front end of the preclinical drug R&D pipeline, such as investigating the structure-activity relationship, high-throughput in vitro screening, and ex vivo studies on single cells, organoids, or tumor spheroids. This review summarizes MSI application in pharmaceutical research accompanied by its technical and methodologic advances serving this central demand.